Model-based analyses of chromate, selenate and sulfate reduction in a methane-based membrane biofilm reactor - Zhen Wang; Xueming Chen; He-Ping Zhao (Environment International, 2022)
Selenate (SeO42−) and sulfate (SO42−) are frequently present together with chromate (CrO42−) in certain industrial wastewaters. SeO42− and CrO42− are required to be reduced while SO42− reduction should be minimized to avoid the production of toxic sulfide. In this study, a modified biofilm model was employed to investigate the interactions between CrO42−, SeO42− and SO42− bioreduction in a methane (CH4)-based membrane biofilm reactor (MBfR). The model was calibrated using steady-state experimental data of two reported CH4-based MBfRs reducing these oxyanions. The modeling results suggested that the majority of methanotrophs (>80%) were located in the outer layer of the biofilm, while the oxyanions-reducing bacteria preferred to grow close to the membrane. The introduction of SeO42− or SO42− enriched selenate/sulfate-reducing bacteria (SeRB/SRB) but decreased the abundance of chromate-reducing bacteria (CRB). A biofilm thickness of >300 μm, an HRT of higher than 4 h and an influent dissolved oxygen concentration of 0.3 mg /L were favorable for simultaneous high-level CrO42− and SeO42− removal. A two-stage MBfR system with optimized operational conditions showed promise in retaining high-purity (>98%) selenium nanoparticles when treating both CrO42− and SeO42− impacted wastewaters. Moreover, the model indicated that efficient CrO42− removal (>90%) along with minor SO42− reduction (<10%) could be realized via maintaining appropriate biofilm thickness (200-250 μm) and influent dissolved oxygen (0.7–0.8 mg /L) in a single MBfR. These findings offer insights for the design and operation of CH4-based technology for remediating CrO42− contaminated industrial wastewaters.